Second Language Acquisition: A Theoretical Introduction to Real World Applications - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2018)
Reviewed by Donna Fernández Nogueira Universidad de Deusto, Spain   Second Language Acquisition: A Theoretical Introduction to Real World Applications by Alessandro G. Benati and Tanja Angelovska (2016) is without doubt a help for undergraduate students and trainee teachers who need to deal with the issue of second language acquisition (SLA). The content is very precise but, at the same time, very clear and easy to understand and follow, even for those students who are dealing with this topic for the first time. It can be applied in the classroom, as a resource book or even a course book, to introduce SLA. It is true that the field has become very complex in the past years, as the studies include many different fields of knowledge: linguistics, psychology, sociology and education. However, the authors of this book have been able to highlight the most important theories in such a way that it can be an excellent resource for use in undergraduate classes. They have also incorporated some activities for students to reflect on the topic and to develop their critical thinking about it. Most of the activities are good and although some are unpretentious, they are effective for students to think about this issue. In short, all of the activities give an insight into the theory.